Ambition and extreme behavior: relative deprivation leads ambitious individuals to self-sacrifice - Resta, Elena; Ellenberg, Molly; Kruglanski, Arie W.; Pierro, Antonio (Frontiers in Psychology, 2023)
Ambitious people are characterized by strong motivation toward great and valuable objectives, with the superordinate goal to gain respect and recognition from others. Recent literature regarding ambition demonstrated that it leads individuals to engage in extreme behavior. However, no previous research has investigated under which conditions the relation between ambition and extremism is enhanced. Across two studies, we tested the hypothesis that ambitious individuals are more prone to engage in extreme behavior in the face of relative deprivation (i.e., justice sensitivity), than their less ambitious counterparts. We confirmed our predictions employing a cross-sectional design with an American sample (Study 1) and an experimental design with an Italian sample (Study 2). The present research adds theoretical knowledge and empirical support to the existing literature on ambition, extreme behavior, and relative deprivation, and provides fruitful insight into strategies for preventing extremism.